HUBUNGAN HEALTH LITERACY DENGAN MASALAH TERKAIT OBAT PASIEN DM TIPE 2 YANG MENDAPATKAN TERAPI INSULIN DI RUMAH DIABETES UBAYA - Reza Amrullah; Lisa Aditama (CALYPTRA, 2018)
Abstract - Health literacy is defined as the extent to which individuals have the ability to obtain, process and understand information from health services. Someone with low level of health literacy tends to misunderstand health information, and vice versa. With low understanding in terms of understanding health information, it is possible to cause several problems,which one of them is drug-related problems. Drug-related problems have a notion of the undesirable events experienced by patients relating to drug therapy where it interferes with the achievement of desired therapeutic goals. This study is a quantitative study with a total of 31 subjects, which aims to determine the relationship between health literacy domain with drug-related problem domain. The relationship gained from each of the instrumentsbeing used, obtained a pro-active relationship affect the patient’s compliance. While the result of statistical analysis using Chi-square test with cross tabulation analysis got significant correlation and the results are; patient attitude toward health influence drug therapy is not required, socio-economic consideration influence drug therapy is not required, and also socio-economic consideration influence ineffectively drug therapy.